An analysis of Romance in Stephenie Meyer's Twilight - Katamona, Bryan Ruswandi; Sabudu, Delli; Kumayas, Tirza A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of research is the analyze of romance in Stephenie Meyer's Twilight. This research categorized as qualitative research .The data collected in the form of words as well as quotation rather than numbers. Objective approach was applied in analyzing the data. The result of the research shows that the love between Bella and Edward reflected of desire to unite the difference between love and vampire, immortal and mortality .The image of vampire as a soul and other one as an evil vampire.